Investigating the Relationship between the Factors and Customer Satisfaction in Online Platform - Gan, Kia Hui; Lim, Wei Sheng; Lim, Sheue Hui; Aronkar, Praveen; Lin, Xinyuan; Binti Meor Hashim, Maisarah; Binti Saadon, Mas Dalyna; Nur Akmalia, Desta Safa; Dewanti, Rosa Ayu; Syafiyyah Putri, Rr. Shafana; Bajpayee, Vedika; Kee, Daisy Mui Hung (Advances in Global Economics and Business Journal, 2024)
The COVID-19 pandemic during the 2020's has led to the rapid growth of e-commerce in recent years, which has necessitated a greater understanding of the factors that contribute to customer satisfaction in the online context. This study was conducted to investigate the relationship between the e-marketing strategies and customer satisfaction in Lazada. The online survey was carried out to collect data and information from 100 respondents. In this study, five independent variables are investigated. The results indicate assurance and responsibility have significant and positive influence on customer satisfaction whereas efficiency has significant and negative impact on customer satisfaction. This study aligns with several Sustainable Development Goals (SDG), such as decent work and economic growth (SDG 8), as well as responsible consumption and production (SDG 12). In conclusion, this study contributes to the existing literature on e-commerce by providing empirical evidence on the impact of e-marketing strategies on customer satisfaction RETRACTION NOTE: The reason for retraction is duplicate publication. The same article has been published in another journal, which is the correct and original version, accessible at: https://ejournal.aibpmjournals.com/index.php/JCDA/article/view/3213 DOI: https://doi.org/10.32535/jcda.v7i2.3213 This publication in AGEBJ is therefore retracted and should not be considered part of the scientific record. We regret the oversight and apologize to our readers.